The Testosterone Effect on Metabolic and Urologic Outcomes in Patients with Nonfunctioning Pituitary Macroadenomas and Hypogonadotropic Hypogonadism - Guadalupe Vargas-Ortega; Gabriel Pérez-Villarreal; Andrés Ramírez de Santiago; Lourdes Balcázar-Hernández; Victoria Mendoza-Zubieta; Oscar Landa-Gutierrez; Carlos Estrada-Robles; Baldomero González-Virla (International Journal of Endocrinology)
Objective. To evaluate cardiovascular risk, metabolic profile, low urinary tract symptoms (LUTS), and sexual function in patients with nonfunctional pituitary macroadenoma (NFPMA) and hypogonadotropic hypogonadism with testosterone therapy (TTh). Methods. A retrospective clinical study at a tertiary care center was performed in 101 men with NFPMA, HH, and TTh; metabolic profile, cardiovascular risk, International Prostate Symptoms Score (IPSS), and International Index of Erectile Function 5 (IIEF-5) scores were evaluated before initiation of TTh and at the last checkup with TTh. Results. Age was 49.3 ± 8.8 years; T before TTh was 195 ng/mL (101–259) vs. 574 (423–774) at the last checkup. The time of TTh administration was 34 months (12–72). An increase in triglyceride levels (200 (153–294) vs. 174 (134–233) mg/dL; p=0.03), dyslipidemia (40% vs. 52%; p=0.03), and MetS (25% vs. 34%; p=0.05) was corroborated. A statistical difference in the Globorisk score and cardiovascular (CV) risk stratification was not found. IIEF-5 score was 15.5 ± 6.5 vs. 17.8 ± 5.3 (p=0.11). An improvement in penetration quality (2.0 ± 1.5 vs. 2.6 ± 1.3; p=0.05), erection after penetration (1.8 ± 1.2 vs. 2.5 ± 1.6; p=0.02), completion of intercourse (1.8 ± 1.2 vs. 2.4 ± 1.3; p=0.03), and satisfaction of sexual intercourse (1.8 ± 1.3 vs. 2.5 ± 1.5; p=0.01) was evidenced. IPSS score was 6 (IQR 2–10) vs. 7 (IQR 4–12); p=0.30. A lower rate of intermittency (14% vs. 3%; p=0.02), urgency (39% vs. 16%; p=0.01), and episodes of nocturia (18% vs. 4%; p=0.02) was found. An increase of hematocrit (44.1 ± 4.4 vs. 47.3 ± 4.4%; p=0.001), hemoglobin (14.9 ± 1.4 vs. 15.9 ± 1.4 g/dL; p=0.001), and prostatic specific antigen (0.59 (0.43–1.19) vs. 0.82 (0.45–1.4) ng/mL; p=0.02) was evidenced during TTh. Conclusion. TTh in young men with NFPMA improves LUTS, sexual function, and some metabolic parameters, and it is relatively safe in the prostatic context.